METODE PENGOLAHAN TANAH TERHADAP PERTUMBUHAN UBI ALABIO (Dioscorea alata L.) - Nurul Istiqomah; Mahdiannoor Mahdiannoor; Fathur Rahman (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
The purpose of tillage for preparing seedbed place, exterminaring weeds, putting in and fusing plant’s residue to the land in order to find the land condition that needed by root so it will increase air circulation, water infiltration, root growth and take the nutrients by the root. The low productivity of alabio’s yam today because the tillage is still traditional in planting, and no specially treatments given to the land. This research has purpose to know the influence of the tillage method to growth alabio’s yam (Dioscorea alata L.). This research is conducted at Pasar Sabtu Village, Sungai Tabukan District, Hulu Sungai Utara Regency from May until June 2015. This study used a Randomized Block Design (RBD) single factor. Factor studied is tillage method, (t0) zero tillage, (t1) minimum tillage, (t2) maximum tillage. Research result shows that the tillage method given is significant to the plant’s height and the number of leaves at the age of 14 and 21 DAP, significant to the rod’s diameter at the age of 42 DAP and very significant to the plant’s height and the leaves at the age of 28, 35 and 42 DAP, and no significant to the rod’s diameter at the age of 14, 21, 28 and 35 DAP. Maximum tillage gives the best growth for alabio’s yam.